Μικροβιολογική ποιότητα έτοιμων προς κατανάλωση σαλατών - Στεργίου, Σοφία (Τμήμα Γεωπονικών Επιστημών, Βιοτεχνολογίας και Επιστήμης Τροφίμων, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
In this present study entitled "Microbiological quality and quality characteristics of salads ready for consumption", the microbiological loads of the RBCs was studied in the first part and in the second part their qualitative characteristics regarding the concentration of antioxidants and total phenols. It is noteworthy that for the first time such microbiological study was conducted in Cyprus. The samples obtained were analyzed for the following parameters: total viable microflora (TVC), microorganisms of the Enterobacteriaceae family, Coliforms, Escherichia coli, Listeria spp., Salmonella spp. and measurement of phenols and antioxidants (DPPH, FRAP, ABTS). The results found that, although the RTEs are ready meals which do not need to be further processed because of their production process, they need to be processed by the consumer in part either with water or with a disinfectant (vinegar, lemon) to cleanse the product. The results showed the presence of high microbial load, as well as pathogenic microorganisms (Escherichia coli, Listeria spp., Salmonella spp.). In addition, high concentrations of total phenols and antioxidants were measured in salad samples, resulting in a high concentration of phytochemicals.
Keywords: Ready to eat salads; Foodborne pathogen microorganism; Phytochemicals; Έτοιμες προς κατανάλωση σαλάτες; Παθογόνοι μικροοργανισμοί; Φυτοχημικά